Pure Altruism or Warm-Glow Altruism? Altruistic Motivation and Gender Differences in Socially Responsible Investment - Chen, Shu (Journal of business ethics, 2026)
We investigate whether the altruistic motivations of investors in the context of socially responsible investment (SRI) are the result of pure altruism (i.e., impact-seeking) or warm-glow altruism, and we explore gender differences in these motivations based on two experimental studies. Study 1 tested university students who were asked to perform a stock bidding task; in this context, a theoretical model was used to distinguish pure altruism from warm-glow altruism. Study 2 involved nonprofessional investors who were asked to perform a simulated stock investment task; the aim of this study was to assess the external validity of the findings obtained in Study 1. Our results reveal that altruistic motivations in SRI generally include both pure altruism and warm-glow altruism. Among female investors, SRI is driven primarily by warm-glow altruism rather than pure altruism, whereas male investors are driven less by warm-glow altruism and more by pure altruism. This study contributes to the SRI literature by innovatively distinguishing among different altruistic motivations through its experimental design and theoretical modeling and by providing the first examination of SRI motivations to focus on the role played by gender in this context. It also offers practical insights for policymakers, managers, and SRI product developers seeking to enhance investors’ altruistic motivations and promote SRI.